Effectiveness of fuzzy approach in maximizing portfolio diversification benefit / Zulkifli Mohamed - Mohamed, Zulkifli (2011)
Uncertainty in stock market investing is remaining unsolved. Investment in portfolio is one of the solutions to minimize the uncertainty effect. Hence, unit trusts become one of the best investment alternatives for the public investors. However, many researchers discovered that unit trusts' performances are not as good as expected. Therefore, fund managers need a new vigorous portfolio selection model in order to maximize the portfolio's diversification benefit. In solving uncertainty issues, fuzzy approaches are widely applied in engineering, computing and management sciences, but in finance, it is still at an infancy stage. Therefore, the study has investigated the effectiveness of the fuzzy approach in solving the uncertainty issues in stock market investing. Using data sample from Bursa Malaysia for the period of January 1998 to June 2009, the study has examined the VBS fuzzy model and the MV model in constructing various types of portfolios in different market trends. Linear programming optimization tool was used to construct the portfolios' efficient frontier. The study discovered that in the whole period, rising and sideway market trends, 70% of the MV portfolios are having higher diversification benefit compared to the VBS fuzzy portfolios. In the falling market trend, the result shows that 90% of the VBS fuzzy portfolios are performing better. Upon the finding, the study has extended the asset return variable in the MV model using fuzzy approach. The effectiveness of the extended MV model then has been tested for portfolio the diversification benefit and the ability to generate cumulative abnormal return.